Efektivitas Media Pembelajaran Video Animasi Untuk Meningkatkan Hasil Belajar Ditinjau Dari Minat Belajar Siswa Di SMP Al Qodiriyah Srono - Rahayu, Novilita Dwi; Gerhani, Febrina; Andrie Wijaya, Shendy (UIR Press, 2024)
This study was motivated by the limited variety of learning media used, which resulted in low student interest and ultimately affected their learning outcomes. There were 40 people who participated in the two sample groups of this study, the experimental group and the control group. The sampling technique applied was purposive sampling. The data obtained was through questionnaires and tests given directly through print outs to seventh grade students at Al-Qodiriyah Junior High School in Srono. The information collected was dissected using a two-way anova test. In this study, the hypothesis test used the N Gain Score test to compare the learning outcomes between the experimental group and the control group. The results of this study show that there is a significant difference between students who have high and low interest, both experimental and control groups. The results also showed the interaction of students' learning outcomes on learning media and learning interest.